COMMUNICATION COMPETENCY FOR TEACHERS OF YAKUT SPECIAL SCHOOL PURWOKERTO: POTENTIAL AND CHALLENGES - Memet Sudaryanto; Nadia Wirdah Ummah; Uki Hares Y; Bivit Anggoro P.N (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
The language skills of teachers in special schools (Sekolah Luar Biasa/SLB) possess specific characteristics and must be continuously improved. Language habituation for special students is a reflection of their daily communication skills. The teacher's need for classroom management for special students becomes a new challenge because teachers are expected to optimize the use of language in the classroom to enhance students' communication skills directly. Based on the background of the problem, it is essential to conduct a clinical pedagogical analysis for teachers in dealing with problems that occur in the classroom, especially in language learning and communication for special students at SLB B Yakut Purwokerto. In order to answer the formulation of the problem, this study employed a qualitative approach to answer the clinical-pedagogical analysis conducted. The analytical instruments include (1) analysis of vocal abilities such as tone, articulation, pronunciation, application of intonation in learning; (2) analysis of self-expression abilities such as mimics and gestures in learning; and (3) the attitude and mentality of communication in learning. Based on the results of the learning analysis, it shows that the teacher's language skills still need to be improved. On a scale of 100, the results of the analysis of four language skills in SLB teacher learning comprise of communication skills which are 8.2, and class management 7.8. The development of communication and interaction-based learning media acquired 7.0 by implementing learning media technology to initiate creative ideas from teachers of SLB B Yakut Purwokerto, which later can be a good atmosphere for other schools. Teachers improve pedagogic knowledge and competence in optimizing learning situations through quality and fun interactive learning. All teachers realize the urgency of mastering speaking skills: emphasizing essential points, intonation, clear articulation; hence, special students can understand the material quickly in enhancing students' abilities.